Li-S Battery: A New Kind of Rechargeable Battery for the Future - ฮอมณี ธันยาภรณ์; มีทอง นงลักษณ์ (KKU Science Journal, 2015)
Rechargeable batteries are energy storage devices that are critical to portable electronic industries such as cell phones, computers, and electric vehicles. It is also the key enabling technology for renewable energy. Lithium-Sulfur is one of the future chemistry options of rechargeable batteries. Compared with lithium- ion batteries currently in use in many applications, this new battery chemistry has many advantages such as the ability to store higher energy, wider working temperature range, cheaper, safer and has lower toxicity. However, the downside is that there are chemical changes that affect the stability of the structure causing a rapid decrease in capacity (i.e. high capacity fading) and shorten its cycle life. Nanotechnology plays a crucial role in solving these problems. As a result, the performance of this new type of battery has been significantly improved. This new battery has the potential to foster widespread use of electric vehicles and renewable energy in a near future.